Predicting Citizen Satisfaction of Local Seaport: A Descriptive Analysis in The Largest Maritime Province in Indonesia - Johan Fahri; Fadhliah M. Alhadar (Journal of International Conference Proceedings, 2021)
With more than thirty thousand islands, local seaports in the Province of North Maluku, the largest maritime province in Indonesia are vital in ensuring the movements of goods and people as a part of equally distributing resources for regional and national development. The users of public goods and services tend to be seen as regular customers as they are in the private sector. In fact, they should be more seen in the context of citizen satisfaction, as they do as customer satisfaction. This research aims to examine the stronger predictors of local seaport users’ satisfaction, as they are seen as citizen satisfaction. This research used predictors identified from an early explorative study and used them to question255 respondents from 9 local seaports across the Province of North Maluku. The descriptive statistics showed that most of the respondents were from Sanana; traveled on the personal purposes; were in the productive groups of age; and were mostly males. In terms of the items of the questionnaires, the least responded answers were more concerned about facility and payment. These results provided a preliminary description on the satisfaction aspects of the local seaport users in the Province of North Maluku—the maritime province.